Post-Crisis Growth and Bankruptcy Policy Reform in Korea: Empirical Evidence - Chin-hee Hahn; Youngjae Lim (Korea Development Institute (KDI), 2002)
The first part of this paper provides some empirical evidence on the patterns of growth in countries hit by the banking crisis. Specifically, we examine whether the banking crisis accompanies changes in medium or long term growth rates and, if so, whether the changes in growth are mainly driven by the changes in TFPG or by the changes in the pace of input accumulation. It is found that per worker GDP growth lacks persistency over the banking crises, suggesting that high-growth countries could become low-growth countries, and vice versa, as they go through the crises. Growth accounting exercise shows that the changes in growth are mainly driven by the changes in TFPG. This conclusion holds regardless of whether we view that the changes in capital stock are induced by the changes in total factor productivity or not. The implications are as follows. First, although predicting post-crisis growth based on pre-crisis growth might not be easy, it might be more fruitful to direct research efforts to understanding why TFPG changes, rather than why the pace of input accumulation changes, in order to understand post-crisis growth outcome. Second, the policies that are important in determining post-crisis growth outcome are likely to be the ones that can explain the changes in medium or long term TFPG. Viewed in this way, the findings of this paper seem at least consistent with the hypothesis that structural reforms matter in post-crisis growth. The second part of the paper focuses on bankruptcy policy among the potentially important determinants of TFPG in Korea. Specifically, we attempt to examine empirically the effect of the post-crisis bankruptcy policy reform on the efficiency in resource allocation. In the analysis, we focus on the policy reform in the court-administered bankruptcy system. By using firm-level data, the paper shows that the post-crisis reform on the courtadministered bankruptcy system made economic efficiency criterion replace social or political criterion in selecting target firms for rehabilitation procedures. This kind of change in the way the court-administered bankruptcy system works has far-reaching consequences. It is because, for the pre-bankruptcy informal arrangements, one of the most effective disciplines comes from the discipline in the court-administered bankruptcy procedures. Except for the small-sized firms with simple capital structure, the court-administered bankruptcy procedures would be usually the last stages for ailing firms to resort to if the interested parties could not agree on the pre-bankruptcy informal arrangements for corporate restructuring. Therefore, in out-of-court administered settlements, the interested parties' incentives would be directly affected by the structure of court-administered bankruptcy settlements. Although this paper focused exclusively on bankruptcy policy reform as one determinant of post-crisis TFPG performance, there might also be other important policies or institutional factors that are potentially important for understanding movements of TFPG. In this sense, it is still premature to make a bold prediction about post-crisis growth in Korea. With this caveat in mind, we believe one should not overlook the important changes in the area of bankruptcy policy after the crisis when projecting the future growth of the Korean economy. Lastly we should bear in mind that the full-fledged effect of the bankruptcy policy reform is likely to be realized over the longer run, in as much as the bankruptcy policy affects the dynamic efficiency of resource reallocation.
Keywords: 330